2015
DOI: 10.1111/ejn.13026
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of cell–substrate interactions between Schwann cells and three‐dimensional fibrin hydrogels containing orientated nanofibre topographical cues

Abstract: The generation of complex three-dimensional bioengineered scaffolds that are capable of mimicking the molecular and topographical cues of the extracellular matrix found in native tissues is a field of expanding research. The systematic development of such scaffolds requires the characterisation of cell behaviour in response to the individual components of the scaffold. In the present investigation, we studied cell-substrate interactions between purified populations of Schwann cells and three-dimensional fibrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
0
17
0
Order By: Relevance
“…On the other hand, the potential for successful regeneration diminishes with time after injury (Xu et al , ), implying that the presence of a growth substrate may be an important factor for functional recovery within a critical window of opportunity. Previous experiments with dorsal root ganglia and Schwann cell explants in 3D gels (Hodde et al , ; Kriebel et al , ) demonstrated the significance of the electrospun fibres for cell migration and axonal elongation. However, an effect of the gel alone cannot be dismissed entirely because no gelatin‐containing conduits without fibres were tested.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, the potential for successful regeneration diminishes with time after injury (Xu et al , ), implying that the presence of a growth substrate may be an important factor for functional recovery within a critical window of opportunity. Previous experiments with dorsal root ganglia and Schwann cell explants in 3D gels (Hodde et al , ; Kriebel et al , ) demonstrated the significance of the electrospun fibres for cell migration and axonal elongation. However, an effect of the gel alone cannot be dismissed entirely because no gelatin‐containing conduits without fibres were tested.…”
Section: Discussionmentioning
confidence: 97%
“…This effect could be enhanced when fibres included biological signals, for example by blending PCL with collagen (c/PCL; Schnell et al , ) or by covalent binding of integrin‐activating peptides (Bockelmann et al , ). This was first shown on two‐dimensional (2D) substrates in vitro and recently transferred to three‐dimensional (3D) substrates with fibres embedded in hydrogels (Hodde et al , ; Kriebel et al , ). The procedure developed in this study is based on 3D spinning of aligned microfibres, which are subsequently embedded in a hydrogel.…”
Section: Introductionmentioning
confidence: 91%
“…For the estimation of cell purity, sample cultures that were seeded onto PLL/laminin‐coated 12 mm glass coverslips were fixed for 30 min in cold 4% paraformaldehyde (in 0.1 M PBS). The cells were processed for double immunofluorescence as previously described (Hodde et al, ) and incubated with a mouse monoclonal antibody against vimentin (V6630, Sigma‐Aldrich) diluted 1:1000, and polyclonal rabbit antibodies against S100β (T8578, Dako, Z0311, Hamburg, Germany) diluted 1:1000.…”
Section: Methodsmentioning
confidence: 99%
“…Hodde et al reported another approach to provide topographical cues to hydrogel systems [18]. Individual frames with aligned polycaprolactone (PCL) electrospun nanofibers were prepared, which were then stacked together (with parallel fiber orientation).…”
Section: Spatial Control Of Hydrogelsmentioning
confidence: 99%